(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Purpose: The purpose of the study is to examine the relationship between customer purchase behavior and risk perception Theoretical framework: Psychoanalytic Theory has been used to provide a better understanding of the impact of human perception on purchase intentions Design/Methodology/Approach: The primary quantitative method has been used with the help of a survey. Findings: It has been observed that India has shown a steady growth in online buying intentions Research, practical work, and social implication: E-commerce industry needs to incorporate risk management strategies to enhance perceived ease at use Originality/ Value: The value of the study is that it provides a better understanding of the customer purchase intentions